2019
DOI: 10.1002/solr.201900130
|View full text |Cite
|
Sign up to set email alerts
|

Differential Space‐Limited Crystallization of Mixed‐Cation Lead Iodide Single‐Crystal Micro‐Plates Enhances the Performance of Perovskite Solar Cells

Abstract: The synthesis of certain asymmetric perovskite single crystals (SCs)-including CH 3 NH 3 PbI 3 , which is used most commonly-for application in highperformance perovskite solar cells (PeSCs), remains very challenging. Herein, a promising but general method, differential space-limited crystallization (DSLC), is described for synthesizing high-quality perovskite single-crystal micro-plates. The thickness of the perovskite SCs is controlled by the difference between the thicknesses of two sets of polytetrafluoroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Recently, it has been reported that the polymeric Lewis base adduct formation with the perovskite precursors can increase the activation energy for nucleation and lead to high crystallinity and improved optoelectronic properties in polycrystalline film. , Organic–inorganic halide perovskites are a promising semiconductor material due to their high light absorption coefficient, large charge carrier lifetime, long carrier diffusion length, and high carrier mobility, which enable a broad range of photovoltaic and optoelectronic applications. In particular, methylammonium lead iodide (MAPbI 3 ) perovskite single crystals show exceptionally low density of traps and long carrier diffusion length and are much better than its polycrystalline thin films due to the absence of grain boundaries and fewer defects in the single crystals. , Typically, the perovskite single crystals are synthesized by lowering solution temperature, antisolvent diffusion, inverse temperature crystallization, and geometry-defined dynamic flow reaction system . One common limitation with most of these methods is that they are time-consuming and take several days to grow the high-quality MAPbI 3 single crystals and hence do not meet the demands of large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the polymeric Lewis base adduct formation with the perovskite precursors can increase the activation energy for nucleation and lead to high crystallinity and improved optoelectronic properties in polycrystalline film. , Organic–inorganic halide perovskites are a promising semiconductor material due to their high light absorption coefficient, large charge carrier lifetime, long carrier diffusion length, and high carrier mobility, which enable a broad range of photovoltaic and optoelectronic applications. In particular, methylammonium lead iodide (MAPbI 3 ) perovskite single crystals show exceptionally low density of traps and long carrier diffusion length and are much better than its polycrystalline thin films due to the absence of grain boundaries and fewer defects in the single crystals. , Typically, the perovskite single crystals are synthesized by lowering solution temperature, antisolvent diffusion, inverse temperature crystallization, and geometry-defined dynamic flow reaction system . One common limitation with most of these methods is that they are time-consuming and take several days to grow the high-quality MAPbI 3 single crystals and hence do not meet the demands of large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…During the synthesis of asymmetrical SCs, the perovskite precursor solution is positioned between two substrates, with the thickness controlled by altering the geometric space (i.e., the distance between the two substrates). [ 33–38 ] As a result, SCs are obtained in a form of thin films, which can improve the charge collection efficiencies and minimize the degree of charge recombination. In the present work, we propose a space‐confined method (V 2 SLC) to grow 2D perovskite SCs.…”
Section: Resultsmentioning
confidence: 99%
“…To validate our assumption, we performed a diffusion test, following the approach described previously (Figure S2, Supporting Information). [ 31,34 ] The upper and lower surfaces of the channels were VB‐FNPD and PTFE, respectively. Precursor solutions were used containing various molar ratios of PEAI.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained grain is over 2 μm, the maximum PCE of the HPSCs reaches to 20.44%. Sung et al 246 developed a promising and general method of differential space‐limited crystallization to synthesize the high‐quality perovskite single‐crystalline micro‐plates. Therein, the thickness of perovskite films was controlled by the difference between thicknesses of two spacers.…”
Section: Film Engineeringmentioning
confidence: 99%